Macrocrise dos direitos humanos no século do terrorismo - Souto, Márcio Flávio Lins de Albuquerque e (2020)
The century of terrorism was inaugurated through 9/11. Since then, the course of history has been conditioned by that episode and the military replicas that followed. The humanitarian crises of today, eg, the genocide of minorities, the rise of xenophobic nationalism, economic protectionism, the destruction of the cultural heritage of humanity, the flight from regional blocs, etc., are consequences of what can be considered the macro-crisis of the 21st century human rights. The construction of a society that promotes the pluralism of cultures, the universality of the values of freedom, democracy, human rights and the market economy through the integration of normative traditions seems to be increasingly distant in the recent context, but the search for this purpose configures as a real duty of the present generation to future ones. The historical chain of the dimensions of terrorism suggested as the general objective of this thesis aims to describe the various forms of manifestation of this phenomenon over the years, as well as to present different legal treatment tools in each case, increasing the theoretical framework with a form of interpretation distinct from those previously known. In the same vein, understanding its double nature as a macro-crisis and triggering other crises can provide a more concrete perspective of defending human rights. The objectives have thematic relevance to the area of concentration and to the line of research “theory and history of law - theory and history of human rights,” through its menu. The research will be guided by methodological plurality, with the deductive method for the threedimensional classification of terrorism in different contexts being highlighted; the epistemological for the double nature and the functionalist for the definition of the elements that may compose the dogmatic-normative content of the middle crimes, in addition to other procedural goals highlighted in the body of the project. Research on terrorism in the post-9/9 context is socially relevant, as it is perhaps the greatest contemporary humanitarian crisis; academic for all human rights study programs considering the consequences that derive from the cases of spectacularization of collective and personal fear in view of the recurring repercussions in the daily life of the international community.